All-cause mortality of hospitalised patients with suspected COVID-19 in Sierra Leone: a prospective cohort study - Justine Davies; Emma Bailey; Olivia Farrant; Sulaiman Lakoh; Daniel Youkee; Andy JM Leather; Stephen Sevalie; Gibrilla Deen; Mamadu Baldeh; Joseph Baio Kamara; James Baligeh Walter Russell (BMJ Open, 2023)
Objectives To study the mortality of patients with COVID-19 in Sierra Leone, to explore the factors associated with mortality during the COVID-19 pandemic and to highlight the complexities of treating patients with a novel epidemic disease in a fragile health system.Study design A prospective single-centre cohort study. Data were extracted from paper medical records and transferred onto an electronic database. Specific indicators were compared between survivors and non-survivors, using descriptive statistics in Stata V.17.Study setting The infectious diseases unit (IDU) at Connaught Hospital in Freetown, Sierra LeoneParticipants Participants were all patients admitted to the IDU between March and July 2020.Aims of study The primary outcome of the study was to examine the all-cause mortality of hospitalised patients with suspected COVID-19 in Sierra Leone and the secondary outcome measures were to examine factors associated with mortality in patients positive for COVID-19.Results 261 participants were included in the study. Overall, 41.3% of those admitted to the IDU died, compared with prepandemic in-hospital mortality of 23.8%. Factors contributing to the higher mortality were COVID-19 infection (aOR 5.61, 95% CI 1.19 to 26.30, p=0.02) and hypertension (aOR 9.30, 95% CI 1.18 to 73.27, p=0.03)Conclusions This study explores the multiple factors underpinning a doubling in facility mortality rate during the COVID-19 pandemic in Sierra Leone . It provides an insight into the realities of providing front-line healthcare during a pandemic in a fragile health system.